2014
DOI: 10.1182/blood-2014-03-559518
|View full text |Cite
|
Sign up to set email alerts
|

Binding of anti–platelet factor 4/heparin antibodies depends on the thermodynamics of conformational changes in platelet factor 4

Abstract: Key Points• Besides clustering, platelet factor 4/polyanion complexes require input of energy to become immunogenic. • Minute differences in chain length determine the induction of antigenicity of PF4.The chemokine platelet factor 4 (PF4) undergoes conformational changes when complexing with polyanions. This can induce the antibody-mediated adverse drug effect of heparin-induced thrombocytopenia (HIT). Understanding why the endogenous protein PF4 becomes immunogenic when complexing with heparin is important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 36 publications
7
91
0
1
Order By: Relevance
“…16 Previous studies indicated that 11 to 12 saccharides constitute the minimal structure length necessary to complex with and induce antigenicity in PF4 to react with HIT antibodies. [21][22][23][24] In this context, fondaparinux, a pentasaccharide, is too small to strongly react with HIT antibodies. These observations suggest that fondaparinux would not be associated with antibody formation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Previous studies indicated that 11 to 12 saccharides constitute the minimal structure length necessary to complex with and induce antigenicity in PF4 to react with HIT antibodies. [21][22][23][24] In this context, fondaparinux, a pentasaccharide, is too small to strongly react with HIT antibodies. These observations suggest that fondaparinux would not be associated with antibody formation.…”
Section: Discussionmentioning
confidence: 99%
“…Low 4Ts scores were associated with a high negative predictive value (NPV) (0.998; 95% confidence interval [CI], 0.970-1.000). 25 On the other hand, intermediate (4)(5) and high (.6) scores had poor positive predictive values for HIT (0.14; CI, 0.09-0.22) and (0.64; CI, 0.40-0.82), respectively, in large part due to subjective differences of individuals using the scoring systems. 25 Based on these findings, the "Choosing Wisely" campaign of the American Society of Hematology recommends against testing for HIT in patients with a low pretest probability.…”
Section: Updates In Diagnosismentioning
confidence: 98%
“…Structural studies by Brandt et al and Kreimann et al suggest that neoepitopes are expressed on PF4/heparin only under energetically favorable conditions that are dually met when PF4 binds to heparins of minimal chain length (.11 saccharides) and exceeds a threshold of energy to induce a conformational change. 3,4 Cai et al extended these findings in 2015 through crystallization of the PF4/ heparin complex using the synthetic fondaparinux as a heparin analog rather than the biologically heterogeneous UFH/LMWH. 5 These studies reveal that heparin stabilizes the PF4 molecule in its tetrameric conformation and, in the process, linearizes itself, allowing additional PF4 tetramers to join the growing complex ( Figure 1) and exposing neoepitopes on PF4 recognized by HIT antibodies.…”
Section: Updates On Hit Pathogenesismentioning
confidence: 99%
“…All aPF4/P Abs bind to immobilized PF4/P complexes in ELISA [48], but only some of them activate platelets in functional assays, e.g. the heparin-induced platelet activation assay (HIPA) [48] or the serotonin release assay (SRA) [49,50].…”
Section: Human-derived Hit Antibodiesmentioning
confidence: 99%
“…the heparin-induced platelet activation assay (HIPA) [48] or the serotonin release assay (SRA) [49,50]. Human-derived aPF4/P Abs compose of three groups, i.e.…”
Section: Human-derived Hit Antibodiesmentioning
confidence: 99%